Dementia in the Acute General Hospital - Prevalence, Practices and Outcomes - POWER, CLODAGH (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2019)
Background The number of people living with dementia in Ireland is projected to increase exponentially in the coming decades. The international literature suggests, however, that the recognition of dementia is poor, even within health-care settings. It also points to systemic inadequacies in the care that people with dementia receive in acute hospitals. Failure to recognise that a person has dementia precludes access to specialist multi-disciplinary services and support organisations. A person with an unrecognised dementia may be vulnerable to receiving treatment with medications which may be unhelpful or harmful. And although a holistic, palliative care-informed approach to dementia care has been widely endorsed as a means of enhancing the quality of life of people with dementia, the emerging literature in this field indicates that the majority do not enjoy the same quality of end of life care as those with nondementia diagnoses. The focus of this research is on how people with dementia are cared for in the Irish acute hospital from initial admission through to discharge and end of life care planning. The aims of this project were designed to be in line with international inpatient-based research on the quality of care available for people with dementia within the acute health-care system. Methods Used Research was carried out among the elderly inpatient population of St. James’s Hospital, Dublin. Data were collected between 2014 and 2016 under the auspices of the Department of Psychiatry for the Elderly and the Mercer’s Institute for Research in Ageing. Interventional studies were carried out with the informed consent of the participants and/or next of kin. Information relevant to the individual studies, exempli gratia (eg.), demographics, details of physical and mental health, social and daily functioning, smoking and alcohol use, were collected contemporaneously. Wellvalidated cognitive screening tools were applied to assess cognitive function and results were normed for age and level of education. Medical and electronic records were examined for information on clinical course, aspects of management, decisionmaking, communication, correspondence and follow-up. Major Findings 1. Dementia and Mild Cognitive Impairment are highly prevalent but underrecognised in the Irish acute hospital 27% of elderly inpatients met the criteria for Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV) dementia of whom just 41% were previously vii recognised as having a cognitive impairment of any kind. The prevalence of dementia increased with age, affecting 41% of those aged 80 years or over. Among the same group, 21% met the criteria for mild cognitive impairment (MCI) of whom only 10% were previously recognised as having a cognitive disability. 2. People with dementia suffer poorer hospital outcomes than those without dementia The mean length of hospital stay for people with dementia was 15 days longer than for those with normal cognition, an association that was strengthened on multivariate analysis. Dementia patients were also less likely to be discharged to their own home once their admission had concluded and were more likely to be readmitted to hospital in the 12 months following discharge, although these associations were attenuated in multivariate models. There was no impact for dementia on mortality at 12 months. A diagnosis of MCI did not appear to have an effect on outcomes. 3. The 6 Item Cognitive Impairment Test (6CIT) is a valid cognitive screening tool in this population. It is conveniently-administered and is viewed positively by patients The 6CIT can accurately detect dementia in this population of patients with a sensitivity of 0.87 and specificity of 0.74 using a cut-point of ≥ 9. The ability of the 6CIT to detect cognitive impairment of any degree may be less accurate but its high sensitivity of 0.89 using a cut-point of ≥ 6 is useful in that a negative result effectively out rules the presence of cognitive impairment. Though it correlates well with the standardised Mini Mental State Examination (sMMSE), the 6CIT takes half the time to administer. Patients were uniformly positive in their experience of the 6CIT with over 98% of participants reporting that they would be happy to encounter the test again. 4. The management of antipsychotic medications among frail, elderly inpatients falls short of best practice Antipsychotic medications were prescribed for a small number of elderly inpatients. Over three quarters of new antipsychotic prescriptions were commenced for the management of delirium and BPSD. Prescribed doses were at the lower end of the therapeutic scale. However, there was scant evidence that consideration was given to non-pharmacological interventions before beginning antipsychotic treatment and there was an apparent lack of consultation with the patient or next of kin around the decision to begin treatment. Half of those prescribed an antipsychotic during admission were discharged on the new drug and communication with follow-up healthcare providers was inadequate. viii 5. The shift to a palliative care-informed model of dementia care has yet to become established practice in Ireland Among a group of inpatients with dementia, there was little evidence that the core principles of the palliative approach to dementia care were routinely applied. Communication within the triad of clinician, patient and carer was inadequate and decision-making happened during times of crisis rather than in anticipation of a future need. Additionally, there was an incremental loss of critical clinical information at key transition points on the journey toward nursing home care.
APPROVED
Keywords: Acute Hospital; Dementia; Cognitive Screening; Outcomes